2009
DOI: 10.14429/dsj.59.1508
|View full text |Cite
|
Sign up to set email alerts
|

Series Resistance of Silicon Millimeter Wave (Ka-band) IMPATT Diodes

Abstract: The paper describe a computer-based method to calculate the series resistance R s of a millimeter wave Ka-band packaged IMPATT diode from small signal conductance-susceptance characteristics. The series resistance R s has been calculated at the threshold condition when the small signal conductance of the packaged diode just becomes negative and the device susceptance becomes positive. Again, the value of series resistance R s has been determined from the measurement of threshold current and threshold frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 8 publications
1
15
0
Order By: Relevance
“…They determined the series resistance of the device used as a power source in an oscillator circuit by measuring the threshold current at resonant frequency. Some theoretical and experimental studies were later reported [7, 8] on the electrical series resistance of X- and Ka-band IMPATT diodes. The series resistance of millimeter-wave Ka-band IMPATTs was calculated from small-signal simulation [8] and the same was compared with the experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…They determined the series resistance of the device used as a power source in an oscillator circuit by measuring the threshold current at resonant frequency. Some theoretical and experimental studies were later reported [7, 8] on the electrical series resistance of X- and Ka-band IMPATT diodes. The series resistance of millimeter-wave Ka-band IMPATTs was calculated from small-signal simulation [8] and the same was compared with the experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the errors associated with network analyser and the difficulties associated with the accurate device-circuit modelling, the direct measurement of series resistance is almost impossible (Misawa, 1967;Ray & Gupta, 1988). Several authors have proposed different indirect procedures to measure the series resistance of IMPATT devices (Adlerstein, Holway, & Chu, 1983;Mitra, Das, Kar, & Roy, 1993;Pal, 2009). Out of those methods, the modified Adlerstein method of indirect measurement of series resistance of the device reported by Mitra et al (1993) is the most promising and accurate one.…”
Section: Simulation Methods To Estimate Series Resistance Of Impatt/mimentioning
confidence: 99%
“…Out of those methods, the modified Adlerstein method of indirect measurement of series resistance of the device reported by Mitra et al (1993) is the most promising and accurate one. Figure 3 shows an equivalent circuit for packaged IMPATT device (Adlerstein et al, 1983;Brooker, 2006;Pal, 2009). In Figure 3, G and B are the negative conductance and susceptance of the device, respectively.…”
Section: Simulation Methods To Estimate Series Resistance Of Impatt/mimentioning
confidence: 99%
See 2 more Smart Citations